2022
DOI: 10.1111/cdev.13887
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of Korean and heritage language proficiencies and their association with maladjustment among Korean multicultural adolescents

Abstract: This study identified changes in Korean and heritage language proficiencies across five waves (2011)(2012)(2013)(2014)(2015) and examined the association between linguistic acculturation trajectories and adjustment (2016) among Korean adolescents with immigrant family backgrounds (N = 1441; 51.21% female; M age(baseline) = 9.97). All adolescents were from multiethnic families with 91.65% comprising a non-Korean Asian mother (e.g., Japan, Philippines, China, Thailand) and Korean father. Parallel process latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The stronger the identity and acceptability of having a dual culture, the easier it is to live with both cultures and the greater the social adaptability of the dual culture individual (de Anda, 1975;Haritatos & Benet-Martínez, 2002;Valentine, 1971). Using the potential growth model of Korean multicultural youth panel data, Park (2022a) and(2022b) confirmed that the relationship between migrant mothers' adaptation to Korean culture and the youth and mothers' adaptation to the culture affects children. Parenting attitudes have been studied in their effects on children's career decisions and on dual culture acceptability.…”
Section: Bicultural Acceptancementioning
confidence: 90%
See 1 more Smart Citation
“…The stronger the identity and acceptability of having a dual culture, the easier it is to live with both cultures and the greater the social adaptability of the dual culture individual (de Anda, 1975;Haritatos & Benet-Martínez, 2002;Valentine, 1971). Using the potential growth model of Korean multicultural youth panel data, Park (2022a) and(2022b) confirmed that the relationship between migrant mothers' adaptation to Korean culture and the youth and mothers' adaptation to the culture affects children. Parenting attitudes have been studied in their effects on children's career decisions and on dual culture acceptability.…”
Section: Bicultural Acceptancementioning
confidence: 90%
“…Here, we define a multicultural family as one that is formed when people from different cultures become part of one family. Immigrants encounter differences due to the necessary shift in their culture and lifestyle to a different environment, but also in absorbing the ideas, norms, practices, and identities of the new culture through social relationships (Park, 2022a(Park, , 2022b. Research on parenting attitudes, job adaptability, and bicultural acceptance has been actively conducted in Korean in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous findings (H. Kim & Moon, 2013;J. Park & Han, 2023), we accounted for demographic variables (shown in Table 1) such as adolescents' sex (male = 0, female = 1), age (continuous), heritage cultural practice (continuous), having lived in the foreign-born parent's home country (no = 0, yes = 1), language communicated with one's foreign-born parent (categorical; reference = Korean), which parent was born outside Korea (0 = Father, 1 = Mother), foreign-born parents' Korean cultural practices (continuous), parent's country of origin (categorical; reference = father from Korea and mother from Japan), father's and mother's education (0 < college graduate, 1 ≥ college graduate), and monthly family income (continuous), assessed at Timepoint 1, were used.…”
Section: Covariatesmentioning
confidence: 94%
“…With specific reference to multicultural families in Korea, adolescents often experience pressure to learn and become fluent in Korean (J. Park & Han, 2023). Many of these adolescents also report feeling less proud of their foreign-born parents, and the heritage culture of the parent's country of origin may be associated with negative stereotypes in Korean society (Ministry of Gender Equality & Family, 2019).…”
Section: Multiple Developmental Processes Of Culturally Stressful Exp...mentioning
confidence: 99%
“…Heritage language ability is also generally associated with positive outcomes. For example, Park and Han (2022) found that multiracial adolescents who were bilingual demonstrated better adjustment than those that were not.…”
Section: Factors Influencing Ethnic Identity (Ei)mentioning
confidence: 99%